Estimating the beginning of the waterpipe epidemic in Syria - Rastam, Samer (BioMed Central, 2004)
BACKGROUND: Waterpipe smoking is becoming a global public health problem, especially in the Eastern Mediterranean region (EMR). METHODS: We try in this study, which is a cross sectional survey among a representative sample of waterpipe smokers in cafes/restaurants in Aleppo-Syria, to assess the time period for the beginning of this new smoking hype. We recruited 268 waterpipe smokers (161 men, 107 women; mean age ± standard deviation (SD) 30.1 ± 10.2, response rate 95.3%). Participants were divided into 4 birth cohorts (≤ 1960, 1961–1970, 1971–1980, >1980) and year of initiation of waterpipe smoking and daily cigarette smoking were plotted according to these birth cohorts. RESULTS: Data indicate that unlike initiation of cigarette smoking, which shows a clear age-related pattern, the nineties was the starting point for most of waterpipe smoking implicating this time period for the beginning of the waterpipe epidemic in Syria. CONCLUSION: The introduction of new flavored and aromatic waterpipe tobacco (Maassel), and the proliferation of satellite and electronic media during the nineties may have helped spread the new hype all over the Arab World.